The relationship between children’s sleep behavior and parental sleep quality - Dóra Hlín Loftsdóttir 1992- (2024)
Sleep is an essential aspect of human existence and profoundly influences overall health and well-being. While extensive research exists on the relationship between adult sleep and various lifestyle factors, the influence of children’s sleep behavior on parental sleep quality has received limited attention. However, several studies have shed light on this subject, revealing a significant connection between parental sleep and children’s sleep patterns. This study, the first one of its kind in Iceland, aimed to explore this relationship further. A total of 2199 parents of children aged 2-9 participated in the study by completing an online questionnaire. The survey included the Pittsburgh Sleep Quality Index and Children’s Sleep Habits Questionnaire, which were utilized to measure the sleep quality of parents and the sleep behavior of children, respectively. Both questionnaires were translated to Icelandic. All three hypothesis put forth in the study were supported, children’s sleep behavior positively correlated with parental sleep quality, mothers had significantly worse sleep quality than fathers and parents of children diagnosed with a neurodevelopmental disorder had worse sleep quality than parents of typically developing children. Svefn er nauðsynlegur þáttur mannlegrar tilveru og hefur djúpstæð áhrif á heilsu og velsæld. Þó að umfangsmiklar rannsóknir séu fyrir hendi varðandi samband svefns og ýmissa lífsstílsþátta, þá hafa áhrif svefnhegðunar barna á svefngæði foreldra fengið takmarkaða athygli. Nokkrar rannsóknir hafa þó varpað ljósi á viðfangsefnið, og sýnt fram á marktækt samband á milli svefns foreldra og svefnmynsturs barna þeirra. Markmið rannsóknar þessar, sem er sú fyrsta sinnar tegundar á Íslandi, er að kanna frekar þetta samband. Þátttakendur í rannsókninni voru 2.199 foreldrar barna á aldrinum 2-9 ára og svöruðu þeir spurningalista sem lagður var fyrir með rafrænum hætti. Spurningakönnunin innihélt m.a. spurningalista sem kallast Pittsburgh Sleep Quality Index og Children´s Sleep Habits ...